Exploring the synergies of a hybrid BCI-VR neurorehabilitation system - Bermúdez i Badia, Sergi (2019)
Stroke is one of the leading causes of adult disability with a high economical and societal cost. In the last years, novel rehabilitation paradigms have been proposed to make use of the life-long plasticity of the brain to regain motor function. We have developed a hybrid BCI-VR system that explores the idea of combining a personalized motor training in a VR environment - exploiting brain mechanisms for action execution and observation - and a neuro-feedback paradigm – using mental imagery – as a way to engage secondary or indirect pathways to access undamaged cortico-spinal tracks. Here we present the development and validation experiments of the system. The EEG data on 9 naïve healthy subjects shows that a simultaneous motor action and motor imagery paradigm is more effective in engaging cortical motor networks to a larger extend. In addition, we have tested and validated a motor imagery driven BCI-VR version of our system with 9 additional healthy subjects. The results show that users are capable of controlling a virtual avatar in a motor training task that dynamically adjusts its difficulty to the capabilities of the user. User self-report questionnaires indicate enjoyment and acceptance of the proposed system.